Performance Enhancement of Magnetic Ball Suspension System Using Hybrid Whale Optimization Algorithm with Simulated Annealing - Ekinci, S.; Demiroren, A.; Hekimoglu, B.; Eker, Erdal (Institute of Electrical and Electronics Engineers Inc., 2019)
In this study, an efficient tuning method based on hybrid whale optimization algorithm with simulated annealing (WOA-SA) for optimum parameters setting of proportional integral derivative (PID) controller for magnetic ball suspension system is presented. High quality solutions can be achieved via WOA-SA algorithm with balanced local and global search capabilities. Comparative analyzes were conducted to evaluate the performance of the WOA-SA tuned PID controller designed to increase the stability profile of the system. The original whale optimization algorithm (WOA) and simulated annealing (SA) algorithm were used for performance comparison of the hybrid algorithm. The graphical and numerical results obtained from the convergence curve, transient response analysis and frequency response analysis showed that the proposed WOA-SA tuned system has a more stable structure. The essence and novelty of this study is the successful implementation of the proposed hybrid algorithm-based controller design procedure to the magnetic ball suspension system. © 2019 IEEE.
Benzetilmis Tavlamali Hibrit Balina Optimizasyon Algoritmasi Kullanarak Manyetik Top Aski Sisteminin Performans Artirimi
3rd International Symposium on Multidisciplinary Studies and Innovative Technologies, ISMSIT 2019 -- 11 October 2019 through 13 October 2019 -- -- 156063
Keywords: hybrid optimization; magnetic ball suspension system; PID controller design; simulated annealing; Whale optimization algorithm; Controllers; Electric control equipment; Frequency response; Magnetism; Proportional control systems; Simulated annealing; Three term control systems; Transient analysis; Two term control systems; Frequency response analysis; Hybrid optimization; Optimization algorithms; PID controller design; Proportional integral derivative controllers; Simulated annealing algorithms; Suspension system; Transient response analysis; Suspensions (components)